A trajetória da primeira geração da família na universidade : contribuições acerca da formação acadêmica na PUCRS - Schuh, Malu Santarem (2017)
This dissertation aims to fulfill the needing to Education Master degree obtaining by Pontifícia Universidade Católica do Rio Grande do Sul (PUCRS). We consider that the main question of this research is the first generation students of a family in them academic trajectory at graduation courses of PUCRS, with the objective to contribute for a quality graduating. These academics are students that entered in the university as the firsts between their family (parents and brothers/sisters). For that, will theory support in the authors ahead: Casartelli; Cunha; Dubar; Josso; Mancebo; Morosini; Ristoff; Rocha; Santos; Zabalza, among others, beyond the educational policies figuring out in brazilian scenario. Got realized a case´s study (YIN, 2010) in PUCRS, being adopted this strategies: a) qualitative research (MALHOTRA, 2006) in exploratory way, using depth semistructured interviews, with direct approach and; b) quantitative research (MALHOTRA, 2006), where will be realized a questionnaire with a representative sample from students to quantify the categorized data. The data analysis and interpretation occurred from the Discoursive Text Analysis (DTA) proposal of Moraes e Galiazzi (2011) and into descriptive statistics according to Malhotra (2006). As mainly results we have the students profile characterization that concerns the first generation students of a family in a university, the challenges and possibilities on the academic trajectory progress, the family support importance in graduation way and the university´s space. The conclusions directed for the information access, sighting to offer aids for the universities to institutional policies edification, supporting an articulating work with academic community, helping for the first generation student be included in his own graduating and foment discussions about this theme.